Research progress of combined treatment of western medicine in children with allergic purpura (儿童过敏性紫癜西药联合治疗的研究进展) - HU Yuan (胡园); CHEN Xiuying (陈秀英); LIU Lili (刘莉莉) (中西医结合护理)
Allergic purpura, as an allergic microvascular allergic disease, mostly occurs in children. Clinical manifestations include skin purpura, joint pain, abdominal pain and kidney damage. Severe or delayed treatment may lead to gastrointestinal bleeding, renal failure and even death. In recent years, due to environmental changes, the incidence of this disease has increased year by year, and the number of children has gradually increased. At present, there is no specific medicine for children allergic purpura clinically, but a number of scholars found that the combined use of common drugs such as monoculist sodium and glucocorticoid has a good effect. On the basis of reading a large number of literatures on the combined use of western medicine in the treatment of children with allergic purpura, this paper summarizes, summarizes and summarizes them in order to provide the basis of medication and new research ideas for the combined treatment of children with allergic purpura. (过敏性紫癜作为过敏性微血管变态反应性疾病多发生于儿童, 临床以皮肤紫癜、关节痛、腹痛和肾脏损害为主要表现, 严重或延误治疗者可出现消化道出血、肾功能衰竭甚至死亡。近年来, 由于环境改变导致该病发病率逐年增高, 患儿数量也在逐渐增多。目前临床对于儿童过敏性紫癜尚无特效治疗方法, 但是多项研究发现将孟鲁司特钠、糖皮质激素等常用药物联合运用效果良好。本文在检索关于西药联合运用治疗儿童过敏性紫癜文献的基础上进行整理、归纳和总结, 以期对临床儿童过敏性紫癜联合治疗提供用药依据和研究新思路。)